2003
DOI: 10.1177/13674935030073002
|View full text |Cite
|
Sign up to set email alerts
|

Parent's Management of their Child's Pain in the Home Following Day Surgery

Abstract: When a child returns home following day case surgery, the parent becomes responsible for the assessment and treatment of their child's pain. Pain is documented as being the most common complication following day case surgery. The study investigated parental management of their child's pain at home following day surgery. A purposive sample of 100 parents of children undergoing day case surgery at a regional paediatric hospital was obtained. Parents were contacted by telephone in their own home 24 hours after da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 25 publications
1
18
0
3
Order By: Relevance
“…Parents have universally expressed a desire to prevent or relieve pain in their children (Kankkunen et al, 2002), and most have reported using or supporting the use of a variety of pharmacologic and non-pharmacologic strategies to do so (Forward et al, 1996;Kankkunen et al, 2003Kankkunen et al, , 2008Jonas, 2003). Despite these findings, parents have been critiqued for undertreating children's pain by withholding prescribed analgesics following surgery (Fortier et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Parents have universally expressed a desire to prevent or relieve pain in their children (Kankkunen et al, 2002), and most have reported using or supporting the use of a variety of pharmacologic and non-pharmacologic strategies to do so (Forward et al, 1996;Kankkunen et al, 2003Kankkunen et al, , 2008Jonas, 2003). Despite these findings, parents have been critiqued for undertreating children's pain by withholding prescribed analgesics following surgery (Fortier et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…The majority of researchers examining parents' management of children's pain have done so in descriptive studies of children after outpatient surgery, usually after tonsillectomy. Based on behavioral observation at home after surgery, 31–77% of parents ( N = 897 combined total of subjects across samples with sample sizes ranging from 50 to 315) reported that their children experienced moderate to severe levels of pain (Fortier et al., 2009; Helgadóttir & Wilson, 2004; Jonas, 2003; Kankkunen, et al., 2003; Rony et al., 2010; Zisk, Grey, Medoff‐Cooper, MacLaren, & Kain, 2008). Furthermore, when children self‐reported pain ( N = 258 combined total of subjects across samples with sample sizes ranging from 34 to 80), they also reported moderate (Huth & Broome, 2007; Sutters et al., 2004; Wilson & Helgadóttir, 2006) to severe (Wiggins & Foster, 2007) mean pain scores.…”
Section: Introductionmentioning
confidence: 99%
“…De même en cas de hernie, le bloc du grand et du petit abdominogénital permet une fermeture du sac péritonéova-ginal avec une douleur postopératoire modérée. Dans notre série, aucun enfant n'a été réadmis pour une douleur postopératoire : l'information aux parents [24], le traitement antalgique systématique et un examen clinique par le médecin référant de ville si nécessaire ont permis de l'éviter.…”
Section: Discussionunclassified
“…Lors du retour à domicile, elle est le prolongement de l'équipe soignante en suivant une information complète et écrite donnée lors de la sortie sur les complications éventuelles et les signes cliniques qui permettent de les dépister. Certains auteurs [24] notent même que cette information des parents semble assurer des suites plus simples, d'autant plus que les correspondants médicaux de ville participent activement à la prise en charge pré-et postopératoire de l'enfant [27].…”
Section: Discussionunclassified